Liposome: a carrier for effective drug delivery - Choudhury, Ananta; Sonowal, Kashmiri; Laskar, Rahela E; Deka, Debasish; Dey, Biplab Kumar (Creative Pharma Assent, 2020)
Liposomes are the spherical vesicles containing one or more phospholipid bilayer, which was first described in the middle of 60s by Bangham. The bilayer vesicles are considered as an efficient carrier for drug delivery, diagnostic agents, and also an effective tool for vaccine delivery. Liposome has been used as a potential carrier for several diseases from cardiovascular disease to bacterial infection and also it has the ability to reducing the toxicity of highly potent drugs and simultaneously utilized to improve pharmacokinetics and therapeutic efficacy. A liposome is a formulation which has the capacity to overcome with the limitation of conventional therapies. For the delivery of liposome ocular and inhalation route are some advanced technology. In poorly water soluble substance pulmonary delivery is very much useful. However liposome based vaccines have been demonstrated in clinical trials and further progress in human trails. This review discusses the mechanism of action, Method of preparation, evaluation, application of liposomal drug delivery system along with the recent developments some of the commercially available products.